2014
DOI: 10.1111/corg.12080
|View full text |Cite
|
Sign up to set email alerts
|

How does Family Control Influence Firm Strategy and Performance? A Meta‐Analysis of US Publicly Listed Firms

Abstract: Manuscript Type Empirical Research Question/Issue A contentious and prominent research question in the management literature is whether publicly listed family firms (FFs) outperform other types of corporations. Through a research synthesis of all available studies on the performance of US FFs, we address this question directly. We also extend the debate by raising three salient follow‐up questions. First, is the performance differential between FFs and non‐FFs attributable to a unique set of strategic choices?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 115 publications
(249 reference statements)
11
99
1
6
Order By: Relevance
“…Second, our findings corroborate research that proposes mediating factors that bridge individual perceptions and firm performance (Chrisman, Chua and Litz, 2003). In the family firm research, examining the family's benefits to the firm has often supported joint examinations at the micro and macro levels (Habbershon and Williams, 1999;Wortman, 1994) with erratic findings (Essen et al, 2015). By including the behaviours motivated by family members' perceptions of their firms, we help to clarify the link between the resource of family and its impact on firm performance (Habbershon, Williams and MacMillan, 2003).…”
Section: Theoretical Implicationssupporting
confidence: 78%
“…Second, our findings corroborate research that proposes mediating factors that bridge individual perceptions and firm performance (Chrisman, Chua and Litz, 2003). In the family firm research, examining the family's benefits to the firm has often supported joint examinations at the micro and macro levels (Habbershon and Williams, 1999;Wortman, 1994) with erratic findings (Essen et al, 2015). By including the behaviours motivated by family members' perceptions of their firms, we help to clarify the link between the resource of family and its impact on firm performance (Habbershon, Williams and MacMillan, 2003).…”
Section: Theoretical Implicationssupporting
confidence: 78%
“…Much of the debate in corporate governance research has focused on the relationship between ownership structure and environmental performance (Walls, Berrone, & Phan, ) given that owners determine firm behavior and, consequently, firm performance (Van Essen et al, ). Although previous studies have found contradictory results (i.e., ownership can be either negatively or positively associated with environmental performance), the theoretical support adopted to explain such behavior mostly comes from agency theory, specifically the principal–principal problem, by which blockholders' needs, interests, and goals vary, and the bargaining power of the dominant coalition may impose particular goals on the business (Boyd & Solarino, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we contribute to the theoretical development of family business studies by explaining how family ownership affects firm behavior and performance (Van Essen et al, 2015). We provide evidence that family businesses have competitive disadvantages regarding human resource management.…”
Section: Contributionsmentioning
confidence: 96%
See 1 more Smart Citation
“…To render our meta-analysis comparable to prior studies on the topic (e.g., Carney et al, 2013;O'Boyle et al, 2012;van Essen et al, 2014), we did not exclude primary studies that used samples consisting only of family firms. When we excluded these, our sample size fell from 380 to 279 firms.…”
Section: Robustness Checksmentioning
confidence: 99%